OPTIMALISASI LUAS LAHAN BERDASARKAN NERACA AIR LONG STORAGE (BENDALI) - Yosehi Mekiuw (Universitas Musamus, Merauke, Papua, 2015)
Optimization crop area based on water balance in reservoir ( bendali ) is calculated based on secondary data of previous studies carried out in the Semangga Jaya village. Extensive wetland contained in glorious Semangga Jaya village is 220 ha and 64.50 ha dry land . The source of water used comes from reservoir with a volume of 60056.29 meter cubic . The land area is calculated based on the calculation of crop water requirements , water flow is available , cropping patterns and irrigation efficiency . From the calculation of optimal land in rice plants average less than the total wetland , while the area of land crops on average more than the total land area , meaning that the need for expansion of land for crops .